ENTREPRENEURSHIP DEVELOPMENT STRATEGY IN GERMANY - Bondarenko, Oleksandr (Social Economics, 2022)
Abstract. Entrepreneurship is an important component of the formation of the society and the economy. Today the question arises, what should be the strategy of its development given the past experience. This article discusses the strategy of entrepreneurship development in Germany. The purpose of this article is to investigate the basis for further strategies for entrepreneurial activity development based on the data from previous years, cultural and social heritage of society as well as to identify the most relevant and possible areas of development, its trajectories and the main problems. I found that entrepreneurship in modern Germany had been influenced by the events of the 20th century, when the country had been divided into two parts. However, the transition period had its positive consequences, such as the exchange of knowledge and approaches in solving certain problems and issues. I determined that the reform of entrepreneurship in Germany had entered a new wave of development, taking into account not only its own history, but also general global trends and needs of the internal market. State programs to support start-up entrepreneurs to facilitate the establishment of their own business and the first steps for its development and scaling were considered. I found that the issues of women’s, institutional and social entrepreneurship were becoming relevant. It is related to the change of base conceptions of personality of woman in society as a main educator of child, to the growing problem of explanation of central role of separate agency in institutional changes and to the desires of people and government to do an enterprise more inclusive through development of social enterprises that play a role of preachers of the alternative going near the decision of social problems. The development of entrepreneurship in Germany has a clear strategy in all its areas. The government, the federal government, and private entrepreneurs are making significant efforts to integrate entrepreneurship into society and spread its ideas among the larger masses and categories of citizens. However, there are still obstacles and some of the necessary concepts of communication between different institutions are missing and need to be refined.